(untitled) (Castilla. Estudios de Literatura, 2022)
The short stories “En la espesura de la noche” (2010) and “Una camarera (expatriada a cualquier lugar del mundo)” (2011) depict the feeling of imprisonment that first-person narrators experience within the rigid borders of Equatorial Guinea and Cuba, respectively, and how they overcome this territorial oppression by loving a woman who dwells beyond the national borders they are unable to trespass. Bearing in mind that the love towards nation-states constitutes a way of perpetuating a nationalist ideology and the reinforcement of national borders over individual free agency (Morrison et al., 2021: 514), this article examines how, in both narratives, the exaltation of a transnational love over that of the nation challenges these nation-state’s “unique discourse,” based on the binary border thinking of inside/outside and us/them, in favor of individual agency and a more transnational way of understanding the world.